Flow cytometry based enumeration and functional characterization of CD8 T regulatory cells in patients with multiple myeloma before and after lenalidomide plus dexamethasone treatment - Raja, Karthick Raja Muthu; Plasil, Martin; Rihova, Lucie; Pelcova, Jana; Adam, Zdenek; Hajek, Roman (Cytometry. Part B, Clinical cytometry, 2013)
BACKGROUND: Multiple myeloma (MM) is a malignancy of plasma cells frequently associated with immune abnormalities. Several studies have confirmed that in MM immune deregulation can be mediated by increased numbers of CD4 T regulatory (Treg) cells, and these cells were also associated with poor outcome. In the present study, we aimed to study CD8 Treg cells before and after lenalidomide plus dexamethasone (len-dex) treatment in MM patients. METHODS: Using flow cytometry, we enumerated and assessed suppressive function of CD8 Treg cells in 16 MM patients before and after len-dex treatment. RESULTS: Numbers of CD8 Treg cells (CD8+CD25hi+FoxP3+) (P<0.01) were significantly increased in MM patients (before treatment) compared to healthy donors. However, no significant changes were observed in CD4 and CD8 T cells. A significant increase in CD8 Treg cells was observed after len-dex treatment compared to pre-treatment but no significant difference was observed in CD4 and CD8 T cells. Proliferation assay data showed that CD8 Treg cells inhibited proliferation of CD4 T cells and IFN-γ secretion in a concentration dependent manner. Suppressive activity of CD8 Treg cells did not differ significantly between healthy donors, untreated and len-dex treated MM patients. A significant abnormal level of IL-10 was observed from proliferation assays of untreated and len-dex treated MM patients compared to healthy donors (P≤0.03). CONCLUSION: Using flow cytometry, we have shown that suppressive CD8 Treg cells are increased in MM patients and len-dex treatment is unable to control these suppressive CD8 Treg cells. © 2013 Clinical Cytometry Society.